Práticas informacionais e a construção da competência crítica em informação: Um estudo na Bamidelê – Organização de Mulheres Negras da Paraíba - Melo, Daniella Alves de (2019)
Nowadays, information is one of the most important tools for coping with historically oppressed social segments, such as black women. Based on this premise, this work aimed to understand if/how the Informational Practices developed by black feminists, they're part of Bamidelê - Organization of Black Women in Paraíba, have contributed to the construction of Critical Information Literacy, which enable them to orient their actions to confront relations of domination/submission of gender and ethnic/racial. For that, it was carried out throughout the work: 1. The survey of the socioeconomic profile of the black feminists who work in Bamidelê; 2. The mapping of Information Practices performed by them; 3. The identification of the Informational Practices that have contributed to the construction of a Critical Information Literacy by these women; 4. The analysis of how the Critical Information Literacy contributes to the confrontation of the relations of domination/submission of gender and ethnic/racial, by the black feminists of Bamidelê. It is a study conducted through field research, with a qualitative approach, where data were collected through semi-structured interviews. It is a correlational research, which aims to relate the concepts of Informational Practices and Critical Information Literacy. The data were analyzed through the thematic content analysis, through the categorization technique, based on the analytical categories discussed in the paper. The research showed that the Information Practices developed by black women happen in two scopes: that of the subject, which refers to the experiences of oppression experienced by these women and their action in the search of strengthening; and that of the institution, which has to do with practices aimed at empowering other women. The Critical Information Literacy, on the other hand, is developed throughout the life, from the Information Practices of these women, and relates with the reflection on its informational needs, the construction of the information in alternative spaces and the development of a critical sense information, these points together contribute, through the mutual strengthening and use of constructed information, to the confrontation of the relations of oppression/submission experienced by them.